BE MORE COMPETITIVE IN HIGHER EDUCATION, URGED TENGKU MAHALEEL - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
LANGKAWI, KEDAH, October 2015 – "We need to constantly observe the competitors and be prepared to compete in all aspects, especially in the higher education sector in developing the human resource," said the member of Universiti Sains Malaysia (USM) Board of Governors, Tengku Tan Sri Dr. Mahaleel Tengku Arif in his presentation on the topic of ‘Higher Education for Global Challenges’ at the National Seminar on Academic Management of Higher Educational Institutions (SPeAK 2015) here recently.